Dual targeting of brain region‐specific kinases potentiates neurological rescue in Spinocerebellar ataxia type 1. (11th March 2021) - Lee, Won‐Seok; Lavery, Laura; Rousseaux, Maxime W C; Rutledge, Eric B; Jang, Youjin; Wan, Ying‐Wooi; Wu, Sih‐Rong; Kim, Wonho; Al‐Ramahi, Ismael; Rath, Smruti; Adamski, Carolyn J; Bondar, Vitaliy V; et al.
Abstract: A critical question in neurodegeneration is why the accumulation of disease‐driving proteins causes selective neuronal loss despite their brain‐wide expression. In Spinocerebellar ataxia type 1 (SCA1), accumulation of polyglutamine‐expanded Ataxin‐1 (ATXN1) causes selective degeneration of cerebellar and brainstem neurons. Previous studies revealed that inhibiting Msk1 reduces phosphorylation of ATXN1 at S776 as well as its levels leading to improved cerebellar function. However, there are no regulators that modulate ATXN1 in the brainstem—the brain region whose pathology is most closely linked to premature death. To identify new regulators of ATXN1, we performed genetic screens and identified a transcription factor‐kinase axis (ZBTB7B‐RSK3) that regulates ATXN1 levels. Unlike MSK1, RSK3 is highly expressed in the human and mouse brainstems where it regulates Atxn1 by phosphorylating S776. Reducing Rsk3 rescues brainstem‐associated pathologies and deficits, and lowering Rsk3 and Msk1 together improves cerebellar and brainstem function in an SCA1 mouse model. Our results demonstrate that selective vulnerability of brain regions in SCA1 is governed by region‐specific regulators of ATXN1, and targeting multiple regulators could rescue multiple degenerating brain areas. SYNOPSIS: The molecular mechanisms of selective neuronal vulnerability in neurodegenerative disorders are largely unknown. Here we report that selective vulnerability in Spinocerebellar Ataxia Type 1 (SCA1, caused by an expansion of polyglutamine‐encoding CAG repeat in ATXN1 ) is partially driven by brain region‐specific regulators of the ATXN1 protein. Genetic screen identifies ZBTB7B as a novel ATXN1 regulator. ZBTB7B regulates ATXN1 via activating RSK3 transcription. RSK3 stabilizes ATXN1 protein by phosphorylating ATXN1 on S776 (also a target of MSK1 in the cerebellum). RSK3 is predominantly expressed in the brainstem whereas MSK1 is expressed in the cerebellum. Reducing RSK3 and MSK1 rescues brainstem and cerebellar neurodegeneration, respectively. Abstract : Selective vulnerability of cerebellar and brainstem neurons in Spinocerebellar Ataxia Type 1 (SCA1) is driven by region‐specific regulators of the ATXN1 protein.